In-silico screening of small molecule inhibitors against Lactate Dehydrogenase (LDH) of Cryptosporidium parvum. (December 2018) - Dhal, Ajit Kumar; Pani, Alok; Mahapatra, Rajani Kanta; Yun, Soon-IL
Graphical abstract: Highlights: In silico identification of novel inhibitors against LDH proteins of C. parvum . A total of 40 compounds were selected for docking studies against CpLDH. CHEMBL1784973 from Pathogen Box was identified as the best inhibitor. Molecular dynamics simulation was used to validate the binding mode of the inhibitor. Abstract: Cryptosporidium parvum is a protozoan parasite which causes waterborne diseases known as Cryptosporidiosis. It is an acute enteric diarrheal disease being severe in the case of immunocompromised individuals and children. C. parvum mainly depends on the glycolysis process for energy production and LDH (Lactate Dehydrogenase) is a key controller of this process. In this study from different in-silico approaches such as structure-based, ligand-based and de novo drug design; a total of 40 compounds were selected for docking studies against LDH. The study reported a compound CHEMBL1784973 from Pathogen Box as the best inhibitor in terms of docking score and pharmacophoric features. Furthermore, the binding mode of the best-reported inhibitor was validated through molecular dynamics simulation for a time interval of 70 ns in water environment. The findings resulted in the stable conformation of the inhibitor in the active site of the protein. This study will be helpful for experimental validation.